Minimally invasive surgery for femoral neck fractures using bone cement infusible hollow-perforated screw in high-risk patients with advanced cancer. (September 2015) - Lin, Patrick P.; Kang, Hyun Guy; Kim, Yong-il; Kim, June Hyuk; Kim, Han Soo
Abstract Objective Pathologic or osteoporotic femoral neck fractures usually treated with joint replacement surgery rather than joint-preserving surgery because multiple screw fixation has a high risk for fixation failure and nonunion as well as the need for a postoperative protection period. However, joint-preserving surgery might be preferable in high-risk patients with short life expectancy due to advanced disease. Recently introduced hollow-perforated screws are devices for achieving percutaneous fixation by simultaneous injection to the weak bone area through its multiple side holes. We report our experience of surgical treatment of femoral neck fractures by controlled bone cement injection into the femoral head and neck through a modified hollow-perforated screw in patients with advanced cancer. Methods We modified the hollow perforated screw with variable placing of screw-side holes as fracture patterns. Polymethylmethacrylate (PMMA) bone cement was injected through the screw holes to control its injection into the selective areas of the femoral head and neck while avoiding the fracture sites. One or two of these were fixed percutaneously in 12 patients who have Garden stage I or II femoral neck fractures in the advanced state of advanced cancer. Seven patients had pathologic fracture by metastatic cancer, but 5 had osteoporotic fractures. Results Eleven patients died a mean of 4.1 months after surgery and 1 patient lived with ability to walk for 48 months. Sixteen modified hollow perforated-screws and 16 standard cannulated screws were used for fixation. The mean volume of cement injection was 13.8 ml. The complication developed in 4 patients: cement leakage to the hip joint in 2 patients, subtrochanteric fracture in 1 patient (5 months after surgery) and fixation failure in 1 patients (2 months after surgery). Nine patients could walk with or without a walking aid, and all others also could return to the prefracture-ambulation state with effective pain relief on the third postoperative day. Conclusion This current surgical method could be useful in patients with short life expectancy because of quick pain relief, early return to ambulation, simple operative procedures and short hospital stay. The modified hollow perforated screw which has a diversity of side hole locations for the regulation of bone cement injection into the planned area seems useful for selective femoral neck fractures.